Baking technology and nutrition : towards a healthier world - Cauvain, Stanley P.; Clark, Rosie H., 1966- (Wiley, 2019)
"The proposed work will examine the links between bakery technology and current knowledge and attitudes around human nutrition, and seek to identify the drivers and opportunities for delivering improved nutrition in bakery products in a modern industrial context. A key objective is to provide guidance for students, technologists and scientists active in both nutrition (including health professionals) and baking. While there is much written and talked about the subject of improving the 'healthiness' of baked products, the available information often lacks the cohesion which would enable practical (and consumer-acceptable) delivery of improved nutrition via bakery products. The proposed work will consider examples of the relationship between human nutrition and baking technology, sometimes harmonious, sometimes not, but always challenging for both nutritionists and bakers. It will do so with the intention of improving the dialogue between the two groups and by suggesting templates for future product development which will aid the achievement of common aims. In achieving the latter a thorough understanding of existing and potential future baking technology is required, which the authors are well-placed to provide. A key aim is to provide those involved in human nutrition with a greater appreciation of the technical and production challenges which face bakers when they attempt to develop new products to meet specific nutritional aims, and to highlight for bakers the technical opportunities which can exist for product and process re-formulation to deliver improved nutrition in bakery products, and in doing so, make a positive contribution to improving human nutrition"--